Предмет: Алгебра,
автор: MeaTKnife
Помогите пожалуйста решить алгебру,на фото 2 примера,заранее огромное спасибо
Приложения:
Ответы
Автор ответа:
0
Решение смотри в приложении
Приложения:
Автор ответа:
0
Владимир,спасибо,выручил
Автор ответа:
0
5
6^(x-2)-6^(x-3)+6^(x-1)=246
6^(x-3)*(6-1+36)=246
6^(x-3)*41=246
6^(x-3)=246:41
6^(x-3)=6
x-3=1
x=4
6
3^(3x+1)-4*3^(3x-3)+3^(3x-2)=80
3^(3x-3)^(81-4+3)=80
3^(x-3)*80=80
3^(3x-3)=1
3x-3=0
3x=3
x=1
6^(x-2)-6^(x-3)+6^(x-1)=246
6^(x-3)*(6-1+36)=246
6^(x-3)*41=246
6^(x-3)=246:41
6^(x-3)=6
x-3=1
x=4
6
3^(3x+1)-4*3^(3x-3)+3^(3x-2)=80
3^(3x-3)^(81-4+3)=80
3^(x-3)*80=80
3^(3x-3)=1
3x-3=0
3x=3
x=1
Приложения:
Похожие вопросы
Предмет: Алгебра,
автор: chinabrawl
Предмет: Физика,
автор: RoseDiamondXD
Предмет: География,
автор: alihansulaymanov2008
Предмет: Математика,
автор: oleskadobudko